Optimization of synthesis of 4-dimetilamino benzalaseton by speed and duration variation of stirring using sodium hydroxide as catalyst - ., Sardjiman; Utami, Dwi; ., Dachlan; Intani, Dei; Susanty, Rinnny F. (Indonesian Journal of Pharmacy, 2007)
Aldol condensation is followed by dehydration used 4-dimetilamino benzaldehida and aseton will produce 4-dimetilamino benzalaseton. A factor which influences the rendement of 4-dimetilamino benzalaseton producing is stirring. Due to of that, should be researched about the speedy influencing of stirring in synthesis of 4-dimetilamino benzalaseton used NaOH as catalyst for production of yield produced.The variation of stirring speed that used in the research are 500 rpm; 700 rpm; 900 rpm. Synthesis process taken place for 5 hours 10 minute. The synthesis compound was isolated and counted its yield. The purification was done by recrystalization using etanol absolute : aquadest and counted its recovery. The identification of synthesis compound was conducted by Infrared Spectrometer and NMR Spectrometer.The result showed that the average from the variation of stirring speed 500 rpm; 700 rpm; 900 rpm in gradually are 78,61 %; 85,0 %; 86,1 %. The ANAVA statistic analyzing that the confidence level of 95 % showed in which many variation of stirring speed hasn't given influence for production of yield was produced. The highest yield has found in stirring speed 700 rpm. From the result of melting point data was found that synthesis was produced in stirring speed 500 rpm possessed melting point 129,4OC Â 131,6OC, 700 rpm possesses melting point 131,63OC -133,13OC, 900 rpm possesses melting point 128,67OC-131,23OC while from result of TLC, The retention factor is 0.2 in average. The identification of synthesis compound was conducted by using Infrared Spectrometer and NMR after were compared with starting material showed that the synthesis product was 4-dimetilamino benzalasetonKey words : Benzalaseton, 4-dimetilamino benzalaseto.